Four Copies of SNCA Responsible for Autosomal Dominant Parkinson's Disease in Two Italian Siblings. (9th November 2015) - Ferese, Rosangela; Modugno, Nicola; Campopiano, Rosa; Santilli, Marco; Zampatti, Stefania; Giardina, Emiliano; Nardone, Annamaria; Postorivo, Diana; Fornai, Francesco; Novelli, Giuseppe; Romoli, Edoardo; Ruggieri, Stefano; et al.
Abstract : Background . Parkinson's disease (PD) is mostly characterized by alpha-synuclein ( SNCA ) aggregation and loss of nigrostriatal dopamine-containing neurons. In this study a novel SNCA multiplication is described in two siblings affected by severe parkinsonism featuring early onset dyskinesia, psychiatric symptoms, and cognitive deterioration. Methods . SNCA dosage was performed using High-Density Comparative Genomic Hybridization Array (CGH-Array), Multiple Ligation Dependent Probe Amplification (MLPA), and Quantitative PCR (qPCR). Genetic analysis was associated with clinical evaluation. Results . Genetic analysis of siblings showed for the first time a 351 Kb triplication containing SNCA gene along with 6 exons of MMRN1 gene in 4q22.1 and a duplication of 1, 29 Mb of a genomic region flanking the triplication. Conclusions . The identification of this family indicates a novel mechanism of SNCA gene multiplication, which confirms the genomic instability in this region and provides data on the genotype-phenotype correlation in PD patients.